2011
DOI: 10.1007/s11748-010-0687-7
|View full text |Cite
|
Sign up to set email alerts
|

Acute empyema with intractable pneumothorax associated with ruptured lung abscess caused by Mycobacterium avium

Abstract: Nontuberculous mycobacterial lung disease rarely features pleural involvement. Therapeutic strategies for this situation have not been well established. We present a case of acute empyema with intractable pneumothorax associated with ruptured lung abscess caused by Mycobacterium avium in an immunocompromised patient. Combined treatment that included multidrug antibiotic therapy and nonresectional surgery resulted in a good outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…Such differences might also affect the prevalence of SSP and its clinical features, thus explaining the discrepancies between the results of the present study and those of Brown et al However, the present results suggesting that right laterality is more common in SSP than in PSP are in agreement with those of Brown et al [30]. This result can be explained by the fact that pulmonary emphysema-associated azygoesophageal recess is more common on the right side than on the left, and since pulmonary emphysema is one of the more common underlying diseases in SSP, right laterality is expected to be relatively more prevalent in SSP than in PSP [31]. …”
Section: Discussionsupporting
confidence: 92%
“…Such differences might also affect the prevalence of SSP and its clinical features, thus explaining the discrepancies between the results of the present study and those of Brown et al However, the present results suggesting that right laterality is more common in SSP than in PSP are in agreement with those of Brown et al [30]. This result can be explained by the fact that pulmonary emphysema-associated azygoesophageal recess is more common on the right side than on the left, and since pulmonary emphysema is one of the more common underlying diseases in SSP, right laterality is expected to be relatively more prevalent in SSP than in PSP [31]. …”
Section: Discussionsupporting
confidence: 92%
“…NTM pleuritis may occur via lymphogenous or hematogenous spread in an immunocompromised situation, such as in case of the acquired immunodeficiency syndrome [14,15] or advanced cancers. However, since NTM is usually less virulent than M. tuberculosis, in most cases, the mechanism of NTM pleuritis was primarily suspected to be the perforation of pulmonary NTM disease or spread of inflammation to the pleura [16,18,19,22,31,32]. Our study revealed that 73% of cases had subpleural cavitation, and most cases were considered to present bronchopleural fistula or pneumothorax according to the radiological findings.…”
Section: Discussionmentioning
confidence: 73%
“…Successful management of MAC-Pleural disease may require a combination of medical and surgical treatment [ [13] , [14] , [15] , [16] , [17] ]. Triple drug macrolide based regimen is less effective in MAC-Pleural disease with a culture conversion rate of 73% compared to 95% in MAC-LD [ 15 ].…”
Section: Discussionmentioning
confidence: 99%